Increasing Access to Oral Health Care for People Living with HIV/AIDS in Rural Oregon - Jones, Jill (Association of Schools of Public Health, 2012)
Access to oral health care for people living with HIV/AIDS is a severe problem. This article describes the design and impact of an Innovations in Oral Health Care Initiative program, funded through the Health Resources and Services Administration HIV/AIDS Bureau's Special Projects of National Significance (SPNS) program, that expanded oral health-care services for these individuals in rural Oregon. From April 2007 to August 2010, 473 patients received dental care (exceeding the target goal of 410 patients) and 153 dental hygiene students were trained to deliver oral health care to HIV-positive patients. The proportion of patients receiving oral health care increased from 10% to 65%, while the no-show rate declined from 40% to 10%. Key implementation components were leveraging SPNS funding and services to create an integrated delivery system, collaborations that resulted in improved service delivery systems, using dental hygiene students to deliver oral health care, enhanced care coordination through the services of a dental case manager, and program capacity to adjust to unanticipated needs.